Laba Asuransi Jiwa Syariah Ditinjau dari Beban Klaim, Hasil Investasi, Underwriting, dan Inflasi - Cahya, Bayu Tri; Habibah, Muzayyidatul; Restuti, Dwi Putri; Hanifah, Umi; Jannah, Ulfiyatul (IAIN Kudus, 2023)
The profit-earning activity of an insurance company is important. Moreover, choosing a better variable can accurately assess the quality of the insurance company’s performance as illustrated by its profit. This study aims to empirically prove and interpret the effect of claim expenses, investment returns, underwriting, and inflation on profits. The population is a full Sharia life insurance company registered with the OJK for the 2016-2021 period, which was selected through purposive sampling and obtained from a sample of 30 annual financial reports. This research is quantitative research with a causality approach through hypothesis testing. The analysis was carried out through panel data regression analysis using EViews. The result of this study accepted one of the four hypotheses that investment returns affect sharia life insurance earnings. Conversely, claim expense, underwriting, and inflation do not affect sharia life insurance profits. Profit is a positive signal to influence outsiders’ assessment of the company’s performance. Proper management of funds can optimize sharia life insurance profits.